2015
DOI: 10.1088/0967-3334/36/6/1137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tidal volume on ventilation inhomogeneity assessed by electrical impedance tomography during controlled mechanical ventilation

Abstract: The global inhomogeneity (GI) index is a parameter of ventilation inhomogeneity that can be calculated from images of tidal ventilation distribution obtained by electrical impedance tomography (EIT). It has been suggested that the GI index may be useful for individual adjustment of positive end-expiratory pressure (PEEP) and for guidance of ventilator therapy. The aim of the present work was to assess the influence of tidal volume (VT) on the GI index values. EIT data from 9 patients with acute respiratory dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Indeed, clinical studies have shown that ventilation with higher levels of PEEP reduces the incidence of atelectasis [6, 41, 42] and improves respiratory system compliance mainly in patients receiving general anesthesia for surgery [43, 44]. Also, higher levels of PEEP could alleviated lung inhomogeneity, decreasing the impact of the stress raisers and the stress concentration due to inflation of well-aerated alveoli adjacent to collapsed or fluid-filled alveoli [45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clinical studies have shown that ventilation with higher levels of PEEP reduces the incidence of atelectasis [6, 41, 42] and improves respiratory system compliance mainly in patients receiving general anesthesia for surgery [43, 44]. Also, higher levels of PEEP could alleviated lung inhomogeneity, decreasing the impact of the stress raisers and the stress concentration due to inflation of well-aerated alveoli adjacent to collapsed or fluid-filled alveoli [45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…37 40 41 Identification of pixel end-expiratory minima before and after a change in ventilator settings (eg, in PEEP) creates a functional EIT image of the local changes in end-expiratory lung volume (EELV) 29. If EIT data are acquired during the forced full expiration then the calculation of the electrical impedance change within the first second of the forced exhalation will image the distribution of local FEV 1 42…”
Section: Functional Eit Imagesmentioning
confidence: 99%
“…One subgroup describes the overall degree of spatial heterogeneity of ventilation. Examples are the global inhomogeneity index36 40 49 or the coefficient of variation,36 42 50 calculated from the maps of tidal impedance variation. Another subgroup describes the orientation of the spatial distribution of functional measures, usually in the anteroposterior direction.…”
Section: Eit Measuresmentioning
confidence: 99%
“…However, this study is the largest one ever carried out in adults for the determination of regional lung function by EIT worldwide to the best of our knowledge. The majority of the existing EIT studies on ventilation distribution focus on mechanically ventilated intensive care patients [14,[28][29][30]. We believe that EIT chest examinations may be beneficial in spontaneously breathing patients with pulmonary diseases like COPD, [6,31] asthma [12,13,32] or cystic fibrosis [11,33,34] as well and that this new functional method has a potential in pneumology.…”
Section: Exsmokersmentioning
confidence: 99%